Promoting conceptual understanding of mathematics in senior phase using meaning equivalence reusable learning objects (MERLO) - Graham, Marien Alet (University of Pretoria, 2021)
Thesis (PhD (Assessment and Quality Assurance))--University of Pretoria, 2021.